How do people who use drugs experience treatment? A qualitative analysis of views about opioid substitution treatment in primary care (iCARE study). Issue 2 (10th February 2021) - Alves, Paula Cristina Gomes; Stevenson, Fiona A; Mylan, Sophie; Pires, Nuno; Winstock, Adam; Ford, Chris
Abstract : Objective: To understand the most significant aspects of care experienced by people in opioid substitution treatment (OST) in primary care settings. Design: Semistructured individual interviews were conducted, following the critical incidents technique. Interview transcripts were analysed following a thematic analysis approach. Participants: Adults aged 18 years or older, receiving OST in UK-based primary care services. Results: Twenty-four people in OST were interviewed between January and March 2019. Participants reported several aspects which were significant for their treatment, when engaging with the primary care service. These were grouped into 10 major themes: (1) humanised care; (2) individual bond/connection with the professional; (3) professionals' experience and knowledge; (4) having holistic care; (5) familiarity; (6) professionals' commitment and availability to help; (7) anonymity; (8) location; (9) collaborative teamwork; and (10) flexibility and changes around the treatment plan. Conclusions: This study included first-hand accounts of people who use drugs about what supports them in their recovery journey. The key lessons learnt from our findings indicate that people who use drugs value receiving treatment in humanised and destigmatised environments. We also learnt that a good relationship with primary care professionals supports their recovery journey, and that treatment plans should be flexible, tailor-made and collaboratively designed with patients.